Procedure for Preparation of Financial Statements at The Regional Financial and Assets Agency (BPKAD) in Banten Province - Nida Amalia (PT. EQUATOR SINAR AKADEMIA, 2021)
The purpose of this research is to find out the application of regional accounting in preparing BPKAD Financial Reports in Banten Province, to find out what obstacles often occur in the financial reporting process at the Regional Financial and Asset Management Agency (BPKAD) in Banten Province. The results showed that the Financial Statements produced by the Regional Financial and Asset Management Agency (BPKAD) of Banten Province consisted of Budget Realization Reports (LRA), Operational Reports (LO), Balance Sheets, Changes in Equity Reports. In preparing the financial statements, the Regional Financial and Asset Management Agency (BPKAD) of Banten Province has prepared its financial reports properly based on Government Regulation No. 71 of 2010. In addition, SIMRAL Finance is an application formed by the Central Government with the aim of realizing quality state financial accountability in the central government towards a more effective government. The advantage of SIMRAL Finance is to facilitate the process of preparing financial reports by inputting data in the SIMRAL Finance application